The Role of Swedakarma in the Manifestation of Ocular Pathological Findings Among Diabetic Patients- A Prospective Observational Study (AYUSHDHARA, 2023)
Diabetes mellitus (DM) is a chronic metabolic disorder involving almost all systems with delayed complications. Ophthalmic complications of diabetes rapidly cause blindness and are preventable with early screening and timely management. There are many modifiable risk factors for ocular complications associated with DM. It is very much essential to identify such risk factors to prevent complications. Swedana (Sudation therapy), the prerequisite for Panchakarma (fivefold purification therapy in Ayurveda) is contraindicated in Prameha and explained as an etiological factor of eye diseases. Swedana can become a risk factor for diabetic eye diseases. Repeated Swedakarma is a common practice to treat neurological complications in diabetic patients. Diabetic patients exposed to Swedakarma are more vulnerable to ocular complications. Aim: To analyse the role of Swedakarma in the manifestation of ocular pathological findings among diabetic patients. Methodology: This hospital-based, prospective observational study was conducted at Government Ayurveda College, Tripunithura. The study participants included 108 diabetic patients with matched cases and controls. The Chi-square test was used to analyze various sudation factors and ocular complications. Result: There is a 3.74-fold increase in ocular complications in patients exposed to Swedakarma, compared to patients who did not receive Swedakarma. Conclusion: There is a significant association between Swedakarma and ocular complications in DM.